P-136 MANAGEMENT OF DIRTY ABDOMINAL WALL SITUATIONS WITH AN OVINE RUMEN BIOLOGIC MESH WITH POLYPROPYLENE REINFORCEMENT. (13th October 2022) - Lopez-Monclus, J; Muñoz Rodriguez, J; Roman García De Leon, L; Grillo Marin, C; Iglesias García, E; Fernandez Rodriguez, M; Robin, A; Lucena De La Poza, J L; Blazquez Hernando, L; Garcia Ureña, M A
Abstract: Aim: To present our initial results of abdominal wall surgery in dirty situations with an ovine rumen (OR) biologic mesh reinforced with polypropylene. Patients and Methods: Five patients with elective abdominal wall surgery in a dirty setting were included. Two cases were previous PTFE mesh infections after IPOM repairs, one case of enteroatmospheric fistula through a previous posterior component separation repair, one deep tissue infection after a MILOS retromuscular repair and one definitive closure after a 8 weeks open abdomen in a liver transplantation patient. In the five cases cultures showed polymicrobian infections. Both PTFE meshes were removed and substituted by the OR biologic mesh. In the enteroatmospheric fistula patient the exposed mesh was resected together with the fistula take down, and a re-Rives was performed. In the case of the MILOS deep tissue infection after two weeks with an open abdomen and a temporary abdominal closure the definitive closure was performed with the biologic mesh in the retromuscular space. In the definitive closure of the liver transplantation patient the mesh was placed intraperitoneally as prophylaxis. Results: In four cases there weren´t any surgical sites ocurrences. In the case of the enteroatmospheric fistula the patient presented a partial fascial dehiscence with mesh exposure, managed with a VAC system. With less than a year follow up no hernia recurrence has taken place. Conclusión: The use of an OR biologic mesh with polypropylene reinforcement seems to be safe in abdominal wall repair in dirty settings, with good results during early follow up.